A dialogic approach to promoting professional development: Understanding change in Hong Kong language teachers' beliefs and practices regarding vocabulary teaching and learning. (November 2022) - Chung, Edsoulla; Fisher, Linda
Abstract: Adopting a sociocultural perspective, this paper reports on a case study that examined how a dialogic approach contributed to Hong Kong English teachers' professional development in methods of vocabulary instruction. Data were drawn from interviews, lesson observations, professional dialogues, and reflective writing to present two in-depth contrasting cases. While one teacher reported marked change in her beliefs and practice, the other adapted her practice minimally despite reporting belief changes. The findings revealed the role of dialogic reflection in facilitating professional learning and noted the potential impact of Chinese culture on teachers' dialogic reflection. Further, they showed that changes in practice are mediated by internalising new ideas, linking teacher beliefs with clear goals and contextual factors including institutional policies, time constraints, and learner feedback. Teachers' verbal participation in professional dialogues, for example, showing agreement with the suggestions of others, was insufficient for generating changes in practices. Implications, including the important roles of reflexivity and sociocultural contexts in teacher professional development programmes, along with directions for future research, are considered. Highlights: Social interaction and idea internalisation contribute to teacher development. Exploring beliefs based on multiple lenses fosters professional development. Change in practice is affected by beliefs, reflexivity, and contextual factors. Only overt verbal participation in professional dialogues does not assure change. Culture plays a significant role in teachers' dialogic exchanges of views.